2005
DOI: 10.1002/jemt.20222
|View full text |Cite
|
Sign up to set email alerts
|

Seroreactivity to A‐type retrovirus proteins in a subset of cats with hyperthyroidism

Abstract: The thyroid gland is afflicted in several endocrine, autoimmune, and malignant diseases. Previous studies detected immunoreactivity against proteins of a human intracisternal A-type retroviral particle type-I (HIAP-I) in serum samples from the majority of patients with Graves' disease, an autoimmune disease of the thyroid that can also affect other organs, most prominently the eyes. To determine whether hyperthyroid animals might provide a model for the retroviral involvement in thyroid autoimmunity, serum sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…A link between Yersinia enterocolitica infection and Graves' disease has already been reported (18,19). Recently, several studies have suggested that viral infection caused by enterovirus, influenza B virus, retrovirus or herpesvirus may be involved in the pathogenesis of Graves' disease (6,7,8,20). However, an EBV infection causing infectious mononucleosis has not been reported as a triggering factor of Graves' disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A link between Yersinia enterocolitica infection and Graves' disease has already been reported (18,19). Recently, several studies have suggested that viral infection caused by enterovirus, influenza B virus, retrovirus or herpesvirus may be involved in the pathogenesis of Graves' disease (6,7,8,20). However, an EBV infection causing infectious mononucleosis has not been reported as a triggering factor of Graves' disease.…”
Section: Discussionmentioning
confidence: 97%
“…Environmental factors include infection with bacterium Yersinia enterocolitica (4) or viruses. Among the latter, enterovirus, influenza B virus, retrovirus, and herpesvirus have been previously reported (5)(6)(7)(8). However, there have been no reports linking Epstein-Barr virus (EBV) infection with Graves' disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both genetic and environmental factors are also believed to contribute to the development of GD; however, etiologies and pathogenesis remain unclear (6). Recently, several studies have suggested that viral infection may be involved in the pathogenesis of GD (2-4). Evidence that infection might be related with GD has been shown by epidemiology, serology, and molecular methods.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology and pathogenesis of GD are still not clear, environmental factors including virus infection are suggested to be involved (1). Among these, retrovirus, enterovirus (especially Coxsackie B virus), and influenza B virus were reported with serologic evidence (2-4). However, there has been no report on hantaan virus infection with GD.…”
Section: Introductionmentioning
confidence: 99%